(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article outlines the basic principles, goals and tasks of managing the electronic warfare system of the armed forces at the present stage, as well as the components, forces and facilities of this system and the basic requirements for them.